Helminth infections associated with multiple sclerosis induce regulatory B cells - Correale, Jorge; Farez, Mauricio; Razzitte, Gabriela (Annals of neurology, 2008)
Objective To assess the importance of B‐cell control during parasite infections in multiple sclerosis (MS) patients. Methods Peripheral blood CD19+ B cells from 12 helminth‐infected MS patients, 12 MS patients without infection, 10 patients infected with Trypanosoma cruzi, 8 subjects infected with Paracoccidioides brasiliensis, and 12 healthy control subjects were purified using magnetic cell sorting. Interleukin (IL)‐4, IL‐6, IL‐10, tumor necrosis factor‐α, lymphotoxin, transforming growth factor‐β, brain‐derived neurotrophic factor, and nerve growth factor secretion were evaluated after stimulation with CDw32 L cells and CD40 antibody using enzyme‐linked immunosorbent assays. The production of anti–myelin oligodendrocyte glycoprotein IgG and IgM antibodies was evaluated by enzyme‐linked immunosorbent spot assays. Cell phenotype was assessed by flow cytometry. Results Helminth infections in MS patients created a B‐cell population producing high levels of IL‐10, dampening harmful immune responses through a mechanism mediated, at least in part, by the ICOS‐B7RP‐1 pathway. The IL‐10–producing B‐cell phenotype detected expressed high levels of CD1d and was similar to the one observed in mature naive B2 cells (namely, CD11b−, CD5−, CD27−, and IgD+). Moreover, B cells isolated from helminth‐infected MS patients also produced greater amounts of brain‐derived neurotrophic factor and nerve growth factor compared with those of normal subjects, T. cruzi–infected subjects, P. brasiliensis–infected subjects, or uninfected MS patients, raising the possibility that these cells may exert a neuroprotective effect on the central nervous system. Interpretation Increased production of B‐cell–derived IL‐10 and of neurotrophic factors are part of the parasite's regulation of host immunity and can alter the course of MS, potentially explaining environmental‐related MS suppression observed in areas with low disease prevalence. Ann Neurol 2008